Horse - Brooks, Geraldine (New York, New York Viking, an imprint of Penguin Random House LLC, 2022)
"A discarded painting in a junk pile, a skeleton in an attic, and the greatest racehorse in American history: from these strands, a Pulitzer Prize winner braids a sweeping story of spirit, obsession, and injustice across American history. Kentucky, 1850. Jarrett, an enslaved groom, and a bay foal forge a bond of understanding that will carry the horse to record-setting victories across the South. As the nation erupts in civil war, an itinerant young artist who has made his name painting the racehorse takes up arms for the Union. On a perilous night, he reunites with the stallion and his groom, very far from the glamor of any racetrack. New York City, 1954. Martha Jackson, a gallery owner celebrated for taking risks on edgy contemporary painters, becomes obsessed with a 19th century equestrian oil painting of mysterious provenance. Washington, DC, 2019. Jess, a Smithsonian scientist from Australia, and Theo, a Nigerian-American art historian, find themselves unexpectedly drawn to one another through their shared interest in the horse--one studying the stallion's bones for clues to his power and endurance, the other uncovering the lost history of the unsung Black horsemen who were critical to his racing success. Based on the remarkable true story of the record-breaking thoroughbred, Lexington, who became America's greatest stud sire, Horse is a gripping, multi-layered reckoning with the legacy of enslavement and racism in America"--
111054
Keywords: Race horses -- Fiction; Slavery -- Fiction; Racism -- Fiction; African American horsemen and horsewomen -- Fiction; Painting -- Fiction; Horses in art -- Fiction; Fiction / Historical / General; Fiction / Literary; Kentucky -- Fiction; Historical fiction; Social problem fiction; Domestic fiction; Fictional Work; Novels